Reducing Postoperative Recurrence of Early‐Stage Hepatocellular Carcinoma by a Wound‐Targeted Nanodrug. Issue 20 (7th May 2022) - li, Bozhao; Zhang, Xiuping; Wu, Zhouliang; Chu, Tianjiao; Yang, Zhenlin; Xu, Shuai; Wu, Suying; Qie, Yunkai; Lu, Zefang; Qi, Feilong; Hu, Minggen; Zhao, Guodong; et al.
Abstract: New strategies to decrease risk of relapse after surgery are needed for improving 5‐year survival rate of hepatocellular carcinoma (HCC). To address this need, a wound‐targeted nanodrug is developed, that contains an immune checkpoint inhibitor (anti‐PD‐L1)and an angiogenesis inhibitor (sorafenib)). These nanoparticles consist of highly biocompatible mesoporous silica (MSNP) that is surface‐coated with platelet membrane (PM) to achieve surgical site targeting in a self‐amplified accumulation manner. Sorafenib is introduced into the MSNP pores while covalently attaching anti‐PD‐L1 antibody on the PM surface. The resulting nano‐formulation, abbreviated as a‐PM‐S‐MSNP, can effectively target the surgical margin when intraperitoneally (IP) administered into an immune competent murine orthotopic HCC model. Multiple administrations of a‐PM‐S‐MSNP generate potent anti‐HCC effect and significantly prolong overall mice survival. Immunophenotyping and immunochemistry staining reveal the signatures of favorable anti‐HCC immunity and anti‐angiogenesis effect at tumor sites. More importantly, microscopic inspection of a‐PM‐S‐MSNP treated mice shows that 2 out 6 are histologically tumor‐free, which is in sharp contrast to the control mice where tumor foci can be easily identified. The data suggest that a‐PM‐S‐MSNP can efficiently inhibit post‐surgical HCC relapse without obvious side effects and holds considerable promise for clinical translation as a novel nanodrug. Abstract : a‐PM‐S‐MSNP nanodrug can effectively target the surgical margin, thus generating anti‐HCC immunity and anti‐angiogenesis effect at tumor sites. Excitingly, the a‐PM‐S‐MSNP can efficiently inhibit post‐surgical HCC relapse without obvious side effects and holds considerable promise for clinical translation as a novel nanodrug.